RELEVANCE OF WHOLE BODY VIBRATION EXERCISE IN SPORT: A SHORT REVIEW WITH SOCCER, DIVER AND COMBAT SPORT - Morel, Danielle Soares; Dionello, Carla da Fontoura; Moreira-Marconi, Eloá; Brandão- Sobrinho-Neto, Samuel; Paineiras-Domingos, Laisa Liane; Souza, Patrícia Lopes; Sá- Caputo, Danúbia da Cunha; Dias, Glenda; Figueiredo, Claudia; Carmo, Roberto Carlos Resende; Paiva, Patrícia de Castro; Sousa-Gonçalves, Cintia Renata; et al. (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Whole body vibration exercise (WBVE) has been used as a safe and accessible exercise and important reviews have been published about the use of this exercise to manage diseases and to improve physical conditions of athletes The aim of this paper is to highlight the relevance of WBVE to soccer players, divers and combat athletes. Material and methods: This study was made through a systematic review of publications involving WBVE and the selected sports in two databases (Pubmed and PEDRo). Results: It were identified 10 studies involving WBVE and sports (6 of soccer, 2 of diving and 2 of sport combat) with 156 subjects (80 soccer players, 32 divers and 44 combat athletes), with age from 17 to 44 years old. Conclusion: The use of WBVE has proven to be a safe and useful strategy to improve the physical conditions of players of different sports. These findings may have clinical relevance and should be considered as a strategy to be used to try improve the physical conditions of players.